Comparative Extraction and Quantification of Scutellarein from Leaves of Triumfetta rhomboidea Using RP-HPLC - Kendre, Nutan; Wakte, Pravin (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: The purpose of this paper was to develop a sensitive, reproducible Reverse Phase High Performance Liquid Chromatography (RP-HPLC) for extraction and quantitative estimation of Scutellarein, major flavone glycoside from leaves of Triumfetta rhomboidea. Materials and Methods: To optimize best solvent system and ideal extraction methodology, various leaves extract was prepared by using different solvent systems such as ethanol, ethanol: water (50:50) and water through different extraction methodologies includes, maceration, Soxhlet assisted extraction (SAE), Ultrasound Assisted Extraction (UAE) and Accelerated Solvent Extraction (ASE). Chromatographic separation of Scutellarein was performed on C18 column. Results: The results showed that the highest concentration of Scutellarein was found to be 1.547 ng in ethanolic extract. This study states about, existence of flavone glucocidic content in leaves extract of Triumfetta rhomboidea which can be extracted using ethanol as best solvent system and ASE as optimized extraction methodology. Conclusion: Extracts from T. rhomboidea obtained by maceration, SAE, UAE and ASE methods were analysed by HPLC-ESI-MS/MS to quantify flavonoid scutellarein contents. Ethanol was found to be a promising solvent system and Accelerated Solvent Extraction methodology was found to be the promising methodology for the extraction of Scutellarein from leaves of Triumfetta rhomboidea.
Keywords: Triumfetta rhomboidea; Scutellarein; Accelerated Solvent extraction; Ultrasound Assisted Extraction; RP-HPLC